Changes in the activities of key enzymes and the abundance of functional genes involved in nitrogen transformation in rice rhizosphere soil under different aerated conditions - Chun-mei XU; De-shun XIAO; CHEN Song; CHU Guang; LIU Yuan-hui; ZHANG Xiu-fu; WANG Dan-ying (Journal of Integrative Agriculture, 2023)
Soil microorganisms play important roles in nitrogen transformation. The aim of this study was to characterize changes in the activity of nitrogen transformation enzymes and the abundance of nitrogen function genes in rhizosphere soil aerated using three different methods (continuous flooding (CF), continuous flooding and aeration (CFA), and alternate wetting and drying (AWD)). The abundances of amoA ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB), nirS, nirK, and nifH genes, and the activities of urease, protease, ammonia oxidase, nitrate reductase, and nitrite reductase were measured at the tillering (S1), heading (S2), and ripening (S3) stages. We analyzed the relationships of the aforementioned microbial activity indices, in addition to soil microbial biomass carbon (MBC) and soil microbial biomass nitrogen (MBN), with the concentration of soil nitrate and ammonium nitrogen. The abundance of nitrogen function genes and the activities of nitrogen invertase in rice rhizosphere soil were higher at S2 compared with S1 and S3 in all treatments. AWD and CFA increased the abundance of amoA and nifH genes, and the activities of urease, protease, and ammonia oxidase, and decreased the abundance of nirS and nirK genes and the activities of nitrate reductase and nitrite reductase, with the effect of AWD being particularly strong. During the entire growth period, the mean abundances of the AOA amoA, AOB amoA, and nifH genes were 2.9, 5.8, and 3.0 higher in the AWD treatment than in the CF treatment, respectively, and the activities of urease, protease, and ammonia oxidase were 1.1, 0.5, and 0.7 higher in the AWD treatment than in the CF treatment, respectively. The abundances of the nirS and nirK genes, and the activities of nitrate reductase and nitrite reductase were 73.6, 84.8, 10.3 and 36.5% lower in the AWD treatment than in the CF treatment, respectively. The abundances of the AOA amoA, AOB amoA, and nifH genes were significantly and positively correlated with the activities of urease, protease, and ammonia oxidase, and the abundances of the nirS and nirK genes were significantly positively correlated with the activities of nitrate reductase. All the above indicators were positively correlated with soil MBC and MBN. In sum, microbial activity related to nitrogen transformation in rice rhizosphere soil was highest at S2. Aeration can effectively increase the activity of most nitrogen-converting microorganisms and MBN, and thus promote soil nitrogen transformation.